Study of Efficacy and Safety of Acitretin as Monotherapy in the Treatment of Moderate to Severe Plaque Type Psoriasis (Faridpur Medical College Journal, 2020)
Psoriasis is a chronic papulosquamous disorder with remissions and exacerbations. Varied estimates of the population prevalence of the disease in different parts of the world range from 0.1 - 3%. It is not uncommon in our country. Although there are no treatment options offering a complete cure, a number of options exist for providing symptomatic relief, inducing as well as prolonging remission. Various systemic therapies such as methotrexate, acitretin, cyclosporine, and biologic agents can be used. A review of pharmacokinetics, safety and a discussion of relapse rate establish acitretin, an aromatic retinoid as an efficacious, convenient, oral monotherapy for initial and maintenance of severe psoriasis. A prospective clinical trial was conducted to find out the efficacy and safety of acitretin as monotherapy in the treatment of moderate to severe plaque type psoriasis (PASI range 10-42). Thirty two clinically diagnosed cases of moderate to severe plaque type psoriasis attending the Skin and VD out patient department of Faridpur Medical College Hospital, Faridpur were selected randomly. Majority (46.9%) were between 61 to 80 years of age and only 3.1% patients were in the